From Perception to Error: A Study of Ghanaian Learners’ Errors in Solving Algebra Tasks - Baidoo, Joseph (Unnes Journal of Mathematics Education, 2025)
The nature of algebraic word problems can make such tasks daunting for learners, and this can be further exacerbated by factors including their perceptions. This study explored Ghanaian Junior High School learners’ perceptions of algebraic word problems, how these perceptions are reflected in their errors, and the factors influencing these perceptions and errors. A sequential explanatory mixed-method design was employed to collect data from 200 learners using a test, followed by semi-structured interviews with six learners: three high performers and three low performers. Stratified random sampling was used to recruit learners for the survey, while purposive sampling was applied in selecting learners for the interview. Data were analyzed using descriptive statistics and thematic analysis. The study found that many learners perceived algebraic word problems as “difficult,” “confusing,” or “tricky,” which lowered their confidence and willingness to engage with such tasks. These negative perceptions were closely linked to high rates of comprehension errors (misinterpreting unknowns, 77.5%), transformation errors (reversing subtraction order, 60.5%), and process skill errors (ignoring negative signs, 73.5%). Influential factors included inadequate individualized support from teachers, limited practice, unavailability of textbooks, and large class sizes. It is suggested that mathematics teachers use small-group learning to provide targeted attention and integrate algebraic word problems into daily lessons and assessments. Heads of schools should liaise with Parent-Associations (PAs) to provide adequate textbooks for learners and split classes into streams to reduce overcrowding.